1987
DOI: 10.1002/bjs.1800740737
|View full text |Cite
|
Sign up to set email alerts
|

Model of TPN-associated hepatobiliary dysfunction in the young pig

Abstract: Gallbladder 'sludge' and cholestasis are two common complications associated with total parenteral nutrition (TPN), but the aetiology of each is uncertain. An animal model has been developed in the young pig which demonstrates these two complications. Five female piglets, of Landrace Large White Cross variety weighing 4.5-5.9 kg, received nutritional support for 2 weeks with a continuous infusion of TPN solution at a dose of 150 kcal kg-1 day-1. The solution was 35 per cent dextrose, 5 per cent L-amino acids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Animal models allow co- trolled experimental development of TPN. We have shown that piglets can be maintained for up to 7 days on the same TPN regimes used for human neonates, something that cannot be done in the rat [25] . During TPN, the piglets showed typical responses previously reported in human infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal models allow co- trolled experimental development of TPN. We have shown that piglets can be maintained for up to 7 days on the same TPN regimes used for human neonates, something that cannot be done in the rat [25] . During TPN, the piglets showed typical responses previously reported in human infants.…”
Section: Discussionmentioning
confidence: 99%
“…Most infants on TPN suffer clinical complications, therefore metabolic requirements are complex and data interpretation is difficult [25] . Animal models allow co- trolled experimental development of TPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TPN solution was formulated according to the prescription used by the local neonatal care centre (The William Harvey Hospital, Ashford, Kent). As humans and pigs have similar nutritional requirements [25] it is possible to provide adequate nutritional support in the pig using clinical TPN regimes, which is useful in establishing an animal model with clinical relevance [26].…”
Section: Experimental Designmentioning
confidence: 99%